Konsep Negara: Perbandingan Ibnu Sina dan Mohammad Natsir - Iu Rusliana; Munir Munir; Wawan Sutaji (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Some of the objectives of this research, among others, are to understand the thoughts of Ibn Sina and Mohammad Natsir about the goals of the state, state leaders and similarities as well as differences in the thoughts of Ibn Sina and Mohammad Natsir about goals and state leaders by using a qualitative approach with analytical descriptive methods through library research that The main object is literature which is then compared. The results of this research show that both Ibn Sina and Mohammad Natsir chose a state system based on the Qur'an and hadith, so it is not surprising that Mohammad Natsir revealed that the main goal of the state is to realize Islamic teachings and laws, thus the state's goal is to happiness in this world and the hereafter. According to the two leaders, state leaders must pay attention to their obedience to Allah SWT. From the similarities and differences, the two figures have more similarities than differences, what differs from the two is that Ibn Sina focuses on economic revolution to realize the ideals of the state, while Mohammad Natsir does not specifically discuss the basic problems of the state. We have often found chaos in a country caused by various factors and made people miserable. For this reason, this research tries to find out what the goals of the state are and how the state leaders are both the criteria and requirements for state leaders and the similarities and differences between the concepts of Ibn Sina and Mohammad Natsir.